UPAYA SEKURITISASI PEMERINTAH MALAYSIA DALAM MENANGANI MASALAH PERDAGANGAN MANUSIA DI KAWASAN ASIA TENGGARA TAHUN 2010-2014 - Satria Putra Fajar; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the securitization aspect Government of Malaysia to anticipation of human trafficking in South East Asia in 2010-2014. Nowdays human trafficking are one of criminalization form, and South East Asia regions are the region that has increase of human trafficking. The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the securitization aspect Government of Malaysia to anticipation of human trafficking in South East Asia. The theories applied in this research are security and securitization concept. The conclusion of this research are the securitization aspect Government of Malaysia to anticipation of human trafficking in South East Asia are create a regulations about human trafficking in Malaysia, Government of Malaysia rativication of regulation about trafficking in person, Government of Malaysia deall international agreement with ASEAN to anticipation the human trafficking case.Key words: securitization, human, trafficking, South East Asia.